Extended periods of alcohol intake negatively affects osseointegration in rats - Deco, Camila Porto de [UNESP]; Marchini, Adriana Mathias Pereira da Silva [UNESP]; Marchini, Leonardo; Rocha, Rosilene Fernandes da [UNESP] (American Academy of Implant Dentistry, 2015)
The negative effects of chronic and excessive consumption of alcohol on bone metabolism are reported in the literature. Alcoholism causes a reduction in bone quality and delays fracture repair, among other deleterious effects. However, its effect on osseointegration in dental implants is not fully established. The aim of this research was to investigate the influence of prolonged and excessive consumption of alcohol on osseointegration in rats. Thirty-five female rats, 3 months of age, were divided into five groups according to alcohol consumption period: control (no alcohol), and 3, 4, 5, and 6 months of alcohol consumption. All animals received solid food ad libitum. At 8 months of age, all animals received a dental implant in the right femur, and euthanasia was performed 1 month after the implant placement (final n = 27). Quantification of the percentage of bone-implant direct contact was performed by histomorphometry. Serum levels of calcium and phosphate were also measured. The groups that consumed alcohol for longer periods presented decreased percentages of bone-implant direct contact. The difference was higher in implants apical region. Alcohol consumption did not affect serum calcium levels but raised the level of serum phosphate. Alcohol consumption increased caloric intake but also increased weight loss. It was concluded that chronic and excessive consumption of alcohol can impair osseointegration in rats.
Keywords: Alcohol; Dental implants; Osseointegration